Earthly Adams and Pious Philosophers : A Theological Anthropological Lens to the Sixteenth-Century Astronomical Revolution - Roelants, Nienke, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
Focusing on the works of a select group of Lutheran astronomers in the Wittenberg sphere of influence, Earthly Adams and Pious Philosophers establishes a theological anthropological blueprint that echoed in their contributions to the sixteenth-century astronomical revolution. In challenging canonical cosmology and its Scholastic advocates, Georg Joachim Rheticus, Tycho Brahe, and Caspar Peucer invoked intellectual piety and a pessimist epistemology tailored to Luther's understanding of man after the Fall. The fruitful ignorance to which they submitted can be seen as part of a larger view of the self and the world, the astronomer, the academic scholar and the university, that was essentially theologically informed.